The Circularity of the Embodied Mind - Fuchs, Thomas (Frontiers in Psychology, 2020)
From an embodied and enactive point of view, the mind-body problem has been reformulated as the relation of the lived or subject-body on the one hand, and the physiological or object-body on the other (“body-body problem”). The aim of the paper is to explore the concept of circularity as a means of explaining the relation between the phenomenology of lived experience and the dynamics of organism-environment interactions. This concept of circularity seems also suitable to connect enactive accounts with ecological psychology. It will be developed in a threefold way: (1) as the circular structure of embodiment, which manifests itself (a) in the homeostatic cycles between brain and body, (b) in the sensorimotor cycles between brain, body and environment. This includes the interdependence of an organism’s dispositions of sense-making and the affordances of the environment. (2) as the circular causality which characterizes the relation of parts and whole within the living organism as well as within the organism-environment system; (3) as the circularity of process and structure in development and learning. Here it will be argued that subjective and intersubjective experience constitutes a process of sense-making that entrains (neuro-)physiological processes so as to form modified neuronal structures, which in turn enable altered future interactions. On this basis, embodied experience may ultimately be conceived as the integral of brain-body and body-environment interactions, which has a top-down, formative or ordering effect on physiological processes. This will serve as an approach to a solution of the body-body problem.